Words as Doors in the Poetry of Seamus Heaney and Giorgio Caproni - Masi, Jacopo (2017)
As we all know, some words have the power to open doors (as Ali Baba’s phrase “Sésame, ouvre-toi” in Antoine Galland’s added story to the One Thousand and One Nights) or, more often in our everyday web-connected life, windows. Working as a confirmation, or counterfeiting, of the “trespasser’s” identity, words can allow access to the virtual caves where we store personal information, financial resources, memories. But words are not only keys. As Seamus Heaney stated, commenting the title of his second book of poetry Door into the Dark (Faber and Faber, London, 1969): “Words themselves are doors; Janus is to a certain extent their deity, looking back to a ramification of roots and associations and forward to a clarification of sense and meaning.” If words are doors, then they can open and connect or, on the contrary, separate, hide and deceive, as is the case of the “Morgana door” that the Italian poet Giorgio Caproni used as a metaphor for words: “[...] La porta / condannata... // La porta / cieca, che reca / dove si è già, e divelta / resta biancomurata / e intransitiva... / [...] / La porta / morgana: // la Parola.” Drawing textual examples from the works of the two poets, my paper will compare Heaney’s and Caproni’s poetics, focusing on this double, contradictory nature of the word as sym-bolon (sym-ballein: to unite, bring together) and dia-bolon (dia-ballein: to throw apart, separate).